Development of ternary Mg based alloy for soldering of AZ31B magnesium alloy. (August 2014) - Chen, Y.; Cong, K.; Ma, L.; Yao, Y.; Liu, S.; Long, W.
Abstract : Two kinds of ternary Mg based alloys were designed to join the AZ31B magnesium alloy plates by high frequency induction soldering with argon shielding gas. The microstructures and properties of the filler metals and joints were investigated by SEM, X-ray diffraction, differential scanning calorimetry, spreading test and tensile test. The results have shown that the microstructures of Mg–31·5Al–10Sn filler metal mainly consist of Mg17 Al12, Mg2 Sn and a trace amount of α -Mg phases, while the microstructures of Mg–29·5Zn–1Sn filler metal include α -Mg phase and Mg7 Zn3 with a trace of α -Mg and Mg2 Sn phases. Both of the filler metals have narrow melting zones; however, the spreading area of the Mg–31·5Al–10Sn filler metal is much larger than that of the Mg–29·5Zn–1Sn filler metal on the AZ31B base metal. The average tensile strength of solder joints with Mg–31·5Al–10Sn filler metal is a little higher than that of the latter solder joints with Mg–29·5Zn–1Sn filler metal.